Marco Crumbs BV - Chetan Soman, (SAGE Knowledge. Cases., 2017)
On a windy and extremely cold December day, Ruud van Basten, vice-president manufacturing, was preparing for a likely stormy meeting with marketing vice-president Dirk Jan Gullit and his team later in the week to discuss introducing a new type of extrusion breadcrumbs. He was looking back at what happened in last 10-12 years. It was exciting in the beginning. It was necessary to introduce more products than producing our plain-vanilla type breadcrumbs. It was becoming a commodity product with so many suppliers and very little margin. Introducing more-and-more products was alright till 3-4 years ago. However, our great marketing department now thinks that it is possible to produce anything under the sun. First of all, they keep on adding new products every now and then but I dont recall them dropping any of the products. Secondly, they always come up with wrong forecasts and still complain that we are not responsive in ensuring timely availability of the products.